2019
DOI: 10.3389/fgene.2019.00396
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of DiseaseLand Omics Database for Disease Signatures and Treatments: A Bipolar Case Study

Abstract: Transcriptomics technologies such as next-generation sequencing and microarray platforms provide exciting opportunities for improving diagnosis and treatment of complex diseases. Transcriptomics studies often share similar hypotheses, but are carried out on different platforms, in different conditions, and with different analysis approaches. These factors, in addition to small sample sizes, can result in a lack of reproducibility. A clear understanding and unified picture of many complex diseases are still elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The Warburg influence has emerged in multiple malignant cancers, such as lung cancer, prostate cancer, pancreatic cancer and colon cancer, following more than 90 years of continuing study and testing. Recent findings have shown that aerobic glycolysis plays a significant function in the growth of BC 28 . Metabolism in BC cells showed a higher glycolysis rate and a lower glucose oxidation rate.…”
Section: Discussionmentioning
confidence: 99%
“…The Warburg influence has emerged in multiple malignant cancers, such as lung cancer, prostate cancer, pancreatic cancer and colon cancer, following more than 90 years of continuing study and testing. Recent findings have shown that aerobic glycolysis plays a significant function in the growth of BC 28 . Metabolism in BC cells showed a higher glycolysis rate and a lower glucose oxidation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have delved into the exploration of integrated transcriptomics data through various meta-analyses 48,49 . We opted for the Fisher’s exact test for its straightforward implementation, heightened sensitivity to small sample sizes, non-parametric nature, and platform independence across transcriptomics techniques (such as microarray and RNA-seq).…”
Section: Methodsmentioning
confidence: 99%
“…Differential gene expressions (DGE) were extracted from integrated transcriptomics service from Qiagen Omicsoft database (QIAGEN OmicSoft DiseaseLand 47 ). We extracted both microarray and RNA-seq based transcriptomic (TxP) studies and disease comparisons/contrasts available for all studies in the DiseaseLand in the immunology and inflammation, Internal neurodegenerative and metabolic diseases 48 . Common ontologies were applied to all samples, tissues, diseases, treatments, and comparison types to systematize database curation.…”
Section: Differential Expression In Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The UALCAN online platform (http://ualcan.path.uab.edu/, (accessed on 23 December 2021) was used to compare the transcriptional levels of HOXB9 in CRC compared to other types of cancers and the GEPIA tool (http://gepia.cancer-pku.cn/index.html, (accessed on 27 December 2021)) was used to compare the transcriptional levels of HOXB9 in CRC in comparison with the rest of the HOX genes [17][18][19]. Lastly, the OmicSoft Suite with the integrated OncoLand database (Qiagen, Manchester, UK) was used to assess the HOXB9 gene expression levels in CRC mutant versus wild-type for the top three somatic mutations in CRC which were identified using the COSMIC database (https://cancer.sanger.ac.uk/cosmic, (accessed on 22 June 2020)) [20].…”
Section: Gene Expression Bioinformatics Analysismentioning
confidence: 99%